Peran Modal Sosial Dalam Pengembangan Usaha Sentra Kampoeng Batik Jetis Sidoarjo - Nike Tanzila Hardiyanti; Farida Rahmawati (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
In social life, social capital has an important role in our lives. Social capital has a close relationship in daily life. Basicalls social capital grows from a relationship between individuals and groups in the social system. For them, social capital has economic value that if it can help someone in terms of productivity and efficiency of individuals or groups. Therefore, this important role of social capital is needed in business development, including business development in Kampoeng Batik Jetis Sidoarjo. This study used qualitative descriptive method. Primary data obtained through interviews, observation, and documentation. The results of the study indicate that the role of social capital, trust and networks, has an influential role in the development of the batik industri business in Kampoeng Batik Jetis Sidoarjo. However, there are still obstacles for business actors and craftsmen in developing these businesses, one of which is the lack of cooperation and support in the business development process.